BİSHOP ÇATISINA GÖRE BİR NULL CARTAN EĞRİNİN KARAKTERİZASYONU - İLHAN, MELİKE (Fırat Üniveristesi, 2023)
Bu çalışmada, 4- boyutlu Minkowski uzayında, bir null Cartan eğrinin Bishop çatısına göre k-tip slant helisler ve (k,m)-tip slant helisler için karakterizasyonlar verilmiştir.

In this study, the characterizations are given for k- type slant helices and (k,m)- type slant helices according to the Bishop frame of a null Cartan curve in four-dimensional Minkowski space.
The characterization of a null Cartan curve according to Bishop frame
Keywords: Matematik